2006
DOI: 10.1080/07388940600837490
|View full text |Cite
|
Sign up to set email alerts
|

Just a Phase?: Integrating Conflict Dynamics Over Time

Abstract: Most international conflict research focuses on behavior within a given phase or stage of conflict. Little consideration is given to how actions in one phase affect the dynamics of conflict behavior in subsequent phases. This article postulates several different phases of conflict, gives a numerical overview of past research on those phases, and identifies and assesses several different approaches to integrating those phases, including selection effects, rational choice, path dependency, learning, and issue-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 50 publications
1
20
0
1
Order By: Relevance
“…It was more than three decades ago when Leng (1983, 415), in one of the pioneering studies on recurrent crises, suggested that “we cannot entirely rule out the possibility that some of the bargaining that we observed [during international crises] may be caused by events occurring between the crises.” And yet, while different approaches in the conflict literature agree that international conflicts consist of interlinked phases, the intervals between recurrent confrontations are usually set aside in favor of studying more acute conflict situations. This study challenges such practice and joins a few recent efforts that call greater attention to various segments of a conflict process (Diehl, 2006; Iakhnis and James, 2019; Senese and Quackenbush, 2003). We still know relatively little about respite periods between recurrent confrontations, and even less so about the role they play in conflict escalation.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…It was more than three decades ago when Leng (1983, 415), in one of the pioneering studies on recurrent crises, suggested that “we cannot entirely rule out the possibility that some of the bargaining that we observed [during international crises] may be caused by events occurring between the crises.” And yet, while different approaches in the conflict literature agree that international conflicts consist of interlinked phases, the intervals between recurrent confrontations are usually set aside in favor of studying more acute conflict situations. This study challenges such practice and joins a few recent efforts that call greater attention to various segments of a conflict process (Diehl, 2006; Iakhnis and James, 2019; Senese and Quackenbush, 2003). We still know relatively little about respite periods between recurrent confrontations, and even less so about the role they play in conflict escalation.…”
Section: Discussionmentioning
confidence: 89%
“…The attributes of a previous crisis, such as its level of violence or how it ended, might affect the risk of violent escalation in the next crisis. Such a focus on the past relationships between adversaries is at the heart of the rivalry approach (Colaresi and Thompson, 2002; Diehl, 2006). We know that one confrontation leads to another, and that once states become involved in a conflictual event, they are more likely to experience conflict in the future (Colaresi and Thompson, 2002; Hensel, 1994; Senese and Vasquez, 2008).…”
Section: Research On Crisis Escalation and Precrisis Hostilitiesmentioning
confidence: 99%
“…More recent works have not only paid attention to the occurrence of negotiations, but also explored the interdependence of peace processes (Beardsley 2011;Diehl 2006;Doyle and Sambanis 2006;Findley 2013). Factors that increase the likelihood of negotiations may not always the increase the likelihood of a peace agreement or its successful implementation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the political science and economics literatures, peace is typically identified in relation to war, and in our case, civil war. 2 Scholars typically disaggregate wars into multiple phases-war onset, war intensity and outcome, and war termination and recurrence-and consider the causes and consequences of war in each of these distinct phases with a focus on national-level, as opposed to sub-nationallevel, measures (Walter 2002;Diehl 2006;Findley 2013). Even the scholarship on peacebuilding and peacekeeping uses national-level death threshold measures, defining peace largely as the absence of battle deaths and, in some cases, the presence of a minimum degree of democracy (Doyle andSambanis 2000, 2006;Fortna 2004Fortna , 2008Autesserre 2009Autesserre , 2010.…”
Section: Peace and War In Phasesmentioning
confidence: 99%